Enhanced Indoor Environmental Quality and the Link to Individual Productivity and Organisational Performance: A Scoping Review - Nurick, Saul; Thatcher, Andrew (Journal of African Real Estate Research, 2022)
This paper provides a scoping literature review of research methods that seek to measure individual productivity and organisational performance in office buildings containing enhanced green building features and initiatives that focus on Indoor Environmental Quality (IEQ). The paper follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework and includes thirty-nine academic papers for the period 2000 to 2020. Different research instruments are discussed, including post-occupancy evaluations (POE), longitudinal surveys, and interviews. Furthermore, a narrative focuses on specific measures, including location, amenities, comfort, engagement, individual productivity, and organisational performance. This provides insight into common research approaches and highlights where lesser used research approaches could be applied in the field of green building features and initiatives (GBFIs), including the assessment of individual productivity and organisational performance. Key findings highlight that individual productivity was measured via self-assessment in previous research. At the same time, there has been no research that has successfully measured organisational performance within the context of GBFIs. Gaps have been identified in the literature concerning the relationship between knowledge-based building occupants and measuring/monetising the implementation of GBFIs. Implications of this research indicate that there are common approaches that highlight both strengths and, more importantly, weaknesses concerning linking GBFIs to individual productivity and organisational performance. Addressing weaknesses that predominantly encompass measuring organisational performance creates the opportunity for future research in this field.